THE PERCEPTION OF ENGLISH SENIOR HIGH SCHOOL TEACHERS IN BULELENG DISTRICT ON SCIENTIFIC APPROACH IN THE IMPLEMENTATION OF THE CURRICULUM 2013 - ., I Gede Surya Mertha; ., Prof. Dr. Putu Kerti Nitiasih, MA; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
This study aimed at determining the perception of English senior high school teacher in Buleleng District on Scientific Approach in the implementation of curriculum 2013. The population of this study were English teacher in Buleleng District and selected to be the sample by using random sampling technique. This study was descriptive study with survey technique. The instrument used was only questionnaire with 50 items which was distributed to the sample. The result of this study shows that most teachers in Buleleng District have very good perception on scientific approach in the implementation of curriculum 2013.Kata Kunci : Perception, Scientific Approach, Curriculum 2013 Penelitian ini bertujuan untuk mengetahui persepsi guru bahasa inggris SMA di Kecamatan Buleleng terhadap pendekatan saintifik dalam implementasi kurikulum 2013. Populasi pada penelitian ini adalah guru-guru Bahasa Inggris SMA di Kecamatan Buleleng yang dipilih menjadi sampel dengan teknik acak. Penelitian ini merupakan penetitian deskriptif dengan teknik survey. Istrumen yag digunakan dalam penelitian ini adalah kuesioner dengan 50 butir pernyataan yang didistribusikan pada sampel. Hasil penelitian ini menunjukkan bahwa sebagian besar guru bahasa inggris SMA di Kecamatan Buleleng memiliki persepsi yang baik terhadap pendekatan saintifik dalam implementasi kurikulum 2013.keyword : Persepsi, Pendekatan Saintifik, Kurikulum 2013